2022
DOI: 10.1161/circulationaha.122.062188
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus-Eluting Stents or Bypass Surgery for Multivessel Coronary Artery Disease: Extended Follow-Up Outcomes of Multicenter Randomized Controlled BEST Trial

Abstract: Background: Long-term comparative outcomes after percutaneous coronary intervention (PCI) with everolimus-eluting stent and coronary-artery bypass grafting (CABG) are limited in patients with multivessel coronary artery disease. Methods: This prospective, multicenter, randomized, controlled trial was conducted in 27 international heart centers and was designed to randomly assign 1776 patients with angiographic multivessel coronary artery disease to receive PCI with everolimus-eluting stent or CABG. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…The literature search identified 475 records and 13 studies were considered relevant and then retrieved. Among them, 4 RCTs [BEST (NCT05125367 and NCT00997828) FREEDOM (NCT00086450), PRECOMBAT (NCT03871127 and NCT00422968) and SYNTAX (NCT03417050) (20)(21)(22)(23)] met the eligibility criteria and were included in the final analysis. The PRISMA Flow Chart of study selection is shown in Supplemental Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified 475 records and 13 studies were considered relevant and then retrieved. Among them, 4 RCTs [BEST (NCT05125367 and NCT00997828) FREEDOM (NCT00086450), PRECOMBAT (NCT03871127 and NCT00422968) and SYNTAX (NCT03417050) (20)(21)(22)(23)] met the eligibility criteria and were included in the final analysis. The PRISMA Flow Chart of study selection is shown in Supplemental Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The protocol was approved by the Medical Ethics Committee of Union Hospital, Fujian Medical University. The identity of patients remained anonymous, and the requirement for informed consent was waived due to the observational nature of the study ( 14 , 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…The protocol was approved by the Medical Ethics Committee of Union Hospital, Fujian Medical University. The identity of patients remained anonymous, and the requirement for informed consent was waived due to the observational nature of the study (14,15). PCI was determined by an experienced heart team (interventional cardiologists) based on clinical risk, angiographic characteristics, and patients' preferences.…”
Section: Study Populationmentioning
confidence: 99%
“…In der BEST-Studie wurden Patienten mit Mehrgefäß-KHK zu entweder PCI mittels DES einer neueren Generation (Everolimuseluting Stent) oder CABG randomisiert; in der Subgruppe derjenigen 363 Patienten mit Diabetes mellitus wurde der primäre Endpunkt (Tod, Myokardinfarkt oder Target-Vessel-Revaskularisation nach 2 Jahren) signifikant häufiger nach PCI erreicht [26]; die Daten der verlängerten Beobachtungsdauer (im Mittel 11,8 Jahre) von BEST zeigten zudem bezüglich der Endpunkte Myokardinfarkt und erneute Revaskularisation ein signifikant besseres Abschneiden der CABG gegenüber der PCI [27].…”
Section: Kurzübersichtunclassified